MENINGKATKAN AKTIVITAS BELAJAR SISWA PADA PELAJARAN BAHASA INDONESIA DENGAN MENGGUNAKAN MODEL AIR (AUDITORY, INTELLECTUAL, REPETITION) KELAS V SDN DI MEDAN - Tarigan, Sadari Sri Herlina; Simbolon, Naeklan (Jurnal Dinamika Pendidikan, 2015)
This research aims to improve students learning activities on the subjects of Indonesian language using model AIR (Auditory, Intellectual, Repetition) in the fifth grade. The research was done on March to May 2015. The subjects were students of class V SD with the number of students 20 and the object is the students learning activities in the Indonesian language lessons using AIR models (Auditory, Intellectual, Repetition). The study was conducted by two cycles, one cycle consisting of two meetings. In the first cycle is done the planning, implementation, observation and reflection. Data collection techniques used were observation of student learning activities and observation of activities of teachers. Based on this research, the data can be obtained as follows: In the first cycle of the first meeting, there are 9 people who are active with the percentage of 45% and the second meeting there were 11 people who are active as a percentage: 55%. Silkus II At the first meeting there were 17 people who are active as a percentage: 85% and the second meeting there were 20 people who are active with the percentage of students who are active: 100%. The average value of grade increased each meeting. In the first cycle of meetings I value the class average was 59.73 and the meeting II was 72.17. At the first meeting of the second cycle the average value is 84.01 and the meeting class II is 93.81. The results of the research that has been done and from data analysis can be concluded that by using AIR models (Auditory, Intellectual, Repetition) can improve students learning activities on the subjects of class V SDN Indonesian Medan Helvetia FY 066 046 2014/2015. Therefore, it is suggested that the teachers can use the Model AIR (Auditory, Intellectual, Repetition) in learning.Keywords : Learning activities, learning model, AIR (Auditory, Intellectual, Repetition)